ANALYZING THE EFFECT OF ANTECEDENTS OF TURNOVER INTENTION ACCORDING TO GENERATIONS - (:unkn) unknown (FUTURE ACAD, 2019)
There are many predictors that determine the turnover intention of employees. Among these predictors, mobbing behaviour can be disruptive in the workplace since workplace deviance is a matter which most organizations wrestle today. Organizational commitment is an important variant for employees to achieve organizational success whereas ethical climate is the picture of an organization which demonstrates its' moral philosophy. This study examines the main effects of ethical climate, mobbing, and organizational commitment in predicting turnover intention among the sample of 166 employees, working in a municipality, particularly in Istanbul province, Turkey. The findings indicate that mobbing affect turnover intention positively, while ethical climate has no effect in estimating turnover intention. Study results also suggest that commitment (continuance and affective) is also found to be negatively related to turnover intention of employees. In addition, for Generation-X members, continuance commitment and for Generation-Y members, affective commitment has a significant effect on turnover intention. (C) 2019 Published by Future Academy www.FutureAcademy.org .UK
Keywords: Turnover intention; mobbing; organizational commitment; ethical climate; generations; ORGANIZATIONAL COMMITMENT; JOB-SATISFACTION; ETHICAL CLIMATE; NORMATIVE COMMITMENT; SUPERVISORY TRUST; WORK VALUES; BEHAVIOR; METAANALYSIS; CONTINUANCE; OUTCOMES